SOSIALISASI PUPUK CAIR DARI LIMBAH NANAS DAN PISANG MENGGUNAKAN TRICHODERMA - Siti Chodijah; Sofiah; Adi Syakdani; Liana Aprilayonda; Nadia Yulianti; Ira Wahyuning Thias (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
The community service activity, focusing on technology transfer for liquid organic fertilizer production, aims to utilize environmental potential through household organic waste. This activity was conducted at RT 08 Demang Lebar Daun, Ilir Barat I. The approach included providing educational materials and hands-on demonstrations. The implementation team shared information about various types of organic waste available in the RT 08 Demang Lebar Daun area that could be used as raw materials for liquid fertilizer production. The demonstration involved practical training on making liquid organic fertilizer from household waste, specifically pineapple and banana peels, conducted directly by the service team. The technology transfer of liquid organic fertilizer production offers several benefits, including increasing public knowledge about using organic residues as raw materials, raising awareness of environmental health, and creating economic added value. Furthermore, it allows farmers to reduce fertilizer costs and increase household income through the sale of liquid organic fertilizer.